(untitled) (E Global Congress, 2024)
This article explores the evolution of audio recording to video using Betacam formats, highlighting the role of digital technologies in this process. Starting from Betacam’s analog origins to its digital transformations, it examines the steps involved in converting audio recordings to video, including capturing, editing, and encoding. The advantages of Digital Betacam, such as improved quality, durability, and editing flexibility, are discussed. The impact of digital technologies like DAWs, NLEs, and advanced compression algorithms on audio-video synchronization and production workflows is also analyzed. A case study on the broadcasting industry’s adoption of Betacam formats underscores their significance. The article concludes with perspectives on the future of audio and video production.